Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1111/j.1744-7348.2000.tb00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of winter wheat cultivars for changes in straw composition and digestibility in response to fungicide and growth regulator treatments

Abstract: The effects of a combined fungicide and growth regulator treatment on the composition and dry matter digestibility of straw samples of winter wheat cultivars, Beaver, Brigadier, Hussar, Mercia, Riband, Genesis, Hunter, Spark, Cadenza and Flame, were compared. The samples were analysed for nitrogen, ash, fibre fractions and minerals. Nitrogen content of treated samples was reduced compared to the untreated control samples and in contrast the proportion of ash increased for all the treated samples. All samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Taken together, these suggest that PGR application might increase digestibility; however, in the two studies considering this a consistent pattern was not found. Sharma et al (2000) found that PGRs, when applied with fungicide, increased digestibility though the independent effects of the PGR and fungicides were not determined. Savoie et al (1994) did not find a consistent PGR effect on digestibility, but PGRs were only applied 62 days before harvest, so it is unlikely that they had a large influence on plant form.…”
Section: Crop Managementmentioning
confidence: 89%
See 1 more Smart Citation
“…Taken together, these suggest that PGR application might increase digestibility; however, in the two studies considering this a consistent pattern was not found. Sharma et al (2000) found that PGRs, when applied with fungicide, increased digestibility though the independent effects of the PGR and fungicides were not determined. Savoie et al (1994) did not find a consistent PGR effect on digestibility, but PGRs were only applied 62 days before harvest, so it is unlikely that they had a large influence on plant form.…”
Section: Crop Managementmentioning
confidence: 89%
“…Sharma et al . () found that PGRs, when applied with fungicide, increased digestibility though the independent effects of the PGR and fungicides were not determined. Savoie et al .…”
Section: Crop Managementmentioning
confidence: 92%
“…Thermal analysis can identify changes in proportions of non-structural (carbohydrate), structural (such as ligninhemicellulose complex and cellulose) and inorganic components of grass (Mellon & Sharma, 2002). In the past decade, the application of TG for quality evaluation of cell wall fractions in a range of plant materials including peat (Bergner & Albano, 1993), flax fibre and wheat straw have been reported by Sharma & Kernaghan (1988) and Sharma et al (2000).…”
Section: Introductionmentioning
confidence: 99%